Antimicrobial synergy of silver-platinum nanohybrids with antibiotics - Ranpariya, Bansi; Salunke, Gayatri; Karmakar, Srikanta; Babiya, Kaushik; Sutar, Santosh; Kadoo, Narendra; Kumbhakar, Pathik; Ghosh, Sougata (Frontiers in Microbiology, 2021)
Various bacterial pathogens are responsible for nosocomial infections resulting in critical pathophysiological conditions, mortality, and morbidity. Most of the bacterial infections are associated with biofilm formation, which is resistant to the available antimicrobial drugs. As a result, novel bactericidal agents need to be fabricated, which can effectively combat the biofilm-associated bacterial infections. Herein, for the first time we report the antimicrobial and antibiofilm properties of silver-platinum nanohybrids (AgPtNHs), silver nanoparticles (AgNPs), and platinum nanoparticles (PtNPs) against Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. The AgPtNHs were synthesized by a green route using Dioscorea bulbifera tuber extract at 100 degrees C for 5 h. The AgPtNHs ranged in size from 20 to 80 nm, with an average of similar to 59 nm. AgNPs, PtNPs, and AgPtNHs showed a zeta potential of -14.46, -1.09, and -11.39 mV, respectively. High antimicrobial activity was observed against P. aeruginosa and S. aureus and AgPtNHs exhibited potent antimicrobial synergy in combination with antibiotics such as streptomycin, rifampicin, chloramphenicol, novobiocin, and ampicillin up to variable degrees. Interestingly, AgPtNHs could inhibit bacterial biofilm formation significantly. Hence, co-administration of AgPtNHs and antibiotics may serve as a powerful strategy to treat bacterial infections.
Keywords: antibiofilm; antimicrobial synergy; biogenic synthesis; Characterization; silver-platinum nanohybrids

Catechin-capped silver-doped titanium dioxide nanoparticle enhanced photocatalytic toxic dye degradation - Ghosh, Sougata; Imboon, Tanawat; Layek, Rashbihari; Salunke, Gayatri; Parihar, Vijay Singh; Khumphon, Jeerawan; Webster, Thomas J.; Sutar, Santosh; Kityakarn, Sutasinne; Issro, Chaisak; Khamboonrueang, Dusadee; Thongmee, Sirikanjana (Frontiers in Chemistry, 2025)
Doping-associated surface modification is a powerful strategy to enhance the photocatalytic potential of n-type semiconductor nanomaterials. Silver (Ag) is one of the most effective dopants that can result in the retardation of the electron hole recombination-generating Schottky barrier at the TiO2 interface with a simultaneous extension of absorption to the visible region. This work presents a study on the effect of catechin, a bioactive principle polyphenol compound found in various plants, on the synthesis, Ag-doping and stabilization of TiO2 nanoparticles (TiO2NPs). The nanoparticles were irregular in shape with sizes ranging from 19 to 30 nm. Ag-TiO2NPs were fabricated using TiO2 as a precursor and 1%, 3%, and 5% AgNO3 as a doping agent. The average particle size of 1%Ag-TiO2NPs, 3%Ag-TiO2NPs, and 5%Ag-TiO2NPs was 27.3 +/- 7.5 nm, 29.8 +/- 9.6 nm, and 25.0 +/- 9.0 nm, respectively. High-resolution transmission electron microscopy (HRTEM) showed lattice fringes with an interplanar spacing of 0.23 nm corresponding to the Ag (111) plane in addition to the presence of the anatase phase of TiO2. Fourier transform infrared (FTIR) spectra exhibited a broad peak around 400-800 cm-1 that was attributed to Ti-O-Ti stretching vibrations which was slightly shifted in Ag-TiO2NPs due to changes in the local bonding environment around Ti atoms caused by interactions with Ag. Catechin loading in the TiO2NPs and Ag-TiO2NPs was between 1.55 and 3.3 wt. %. TiO2NPs, 1%Ag-TiO2NPs, 3%Ag-TiO2NPs, and 5%Ag-TiO2NPs exhibited superior photocatalytic degradation of methylene blue dye up to 78%, 87%, 91%, and 92%, respectively, and RhB dye up to 92%, 94%, 97% and 99%, respectively, with a pseudo-first-order reaction kinetics. Furthermore, its recyclability was also demonstrated for three cycles. The simplicity of fabrication and superior photocatalytic performance of TiO2 demonstrated here make this green route advantageous for environmental applications to treat dye contaminated effluent as well as for numerous other applications.
Keywords: catechin; green synthesis; methylene blue dye; Photocatalysis; Rhodamine B; silver doping; titanium dioxide nanoparticles